Titania-based stationary phase in separation of ondansetron and its related compounds - Žižkovský, Václav; Kučera, Radim; Klimeš, Jiří; Dohnal, Jiří (Journal of chromatography. A, Including electrophoresis and other separation methods, 2008)
Improvements in stationary phase stability have been and remain a great task for research of new stationary phases. Metal oxide-based stationary phases appear as one of perspective alternatives to classical silica based stationary phases regarding to their similar effectiveness, different selectivity, different retention mechanism and mainly better chemical and thermal stability. In this study, the retention behaviour of ondansetron and its five pharmacopoeial impurities on TiO(2)-based reversed phase was investigated. The influence of buffer type, pH and concentration on retention was studied. Different types and amount of organic solvent in mobile phase were tested. The effect of temperature and flow rate on separation was investigated. The separation conditions were optimized and developed method validated. The retention parameters - retention time (t(R)), retention factor (k'), theoretical plate number (N), resolution between peaks due to nearby peaks (R(s)) and symmetry factor (A(s)) have been compared to parameters achieved on polybutadiene-coated zirconia column. The thermodynamic parameters of retention of analysed compounds - enthalpy, entropy and Gibbs free energy - were calculated and compared to those achieved on polybutadiene-coated zirconia column. This work proves similarity of retention behaviour of ondansetron and its five related compounds on zirconia-based and titania-based stationary phases and potential utilisation of polyethylene covered TiO(2)-based reversed stationary phase as an alternative to polybutadiene-coated ZrO(2) stationary phase in pharmaceutical analysis of ondansetron.
Keywords: Ondansetron; Chromatography, High Pressure Liquid; Financing, Organized; Titanium; Zirconium; financování organizované; zirkonium; ondansetron; titan; Molecular Structure; vysokoúčinná kapalinová chromatografie; molekulární struktura